PARADIGMA BARU PENINGKATAN MUTU SATUAN PENDIDIKAN DALAM PERSPEKTIF TOTAL QUALITY MANAGEMENT - Mursalim, Mursalim (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2010)
The performance of educational institution as one of public service sector is always the object of criticism by the community who wish a significant change to achieve, at least, the minimum standard. The standard of educational service may function as a guide in planning, actuating and controlling education in terms of actualizing qualified national education. In this case, an operational concept and policy for improving the quality of services through different approach and methods are badly needed. The concept of TQM originally practised in industry would be an alternative to improve the quality of education both at the national and local level.